EEG Characteristics in Cooled and Rewarmed Periods in Post-cardiac Arrest Therapeutic Hypothermia Patients. Issue 4 (July 2017) - Kim, K.; Pargeon, Kimberly L.; Labar, Amy S.; Friedman, Oren; Kandula, Padmaja N.; Labar, Douglas R.
Abstract : Purpose: Continuous video EEG is a tool to assess brain function in injuries, including cardiac arrest (CA). In post-CA therapeutic hypothermia (TH) studies, some EEG features are linked to poor prognosis, but the evolvement of EEG characteristics during two temperature phases and its significance is unclear. We systematically analyzed EEG characteristics in cooled and rewarmed phases of post-CA therapeutic hypothermia patients and investigated their correlation to patient outcome. Methods: This is a retrospective study of EEG analyses, from a single academic center, of 20 patients who underwent CA and therapeutic hypothermia. For each patient, three 30-minute EEG segments in cooled and rewarmed phases were analyzed for continuity, frequency, interictal epileptiform discharges, and seizures. Mortality at the time of discharge was used as outcome. Results: Rewarming was associated with the emergence of interictal epileptiform discharges, 2.6 times as likely compared with the cooled period ( P = 0.03), and was not affected by systemic factors. Continuity, frequency, and discrete seizures were unaffected by temperature and did not show variance within each temperature phase. There was a trend toward the emergence of interictal epileptiform discharges upon rewarming and mortality, but it was not statistically significant. Conclusions: Increased interictal epileptiform discharges with rewarming in post-CA therapeutic hypothermia patients may suggest poor prognosis, but a larger scale prospective study is needed.